High school student prior-knowledge in system thinking on the concept of plant classification system - Q Mukhoyyaroh; S Diana; Amprasto Amprasto (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This research is a preliminary study that aims to investigate the prior-knowledge of high school students in system thinking on the concept of plant classification system. This research method consists descriptive with the participants of 30 students of science class X selected purposively from the high school students population in Bandung city. Students are given multiple choice questions that represent indicators of system thinking. Each correct answer is made a percentage. The results showed that the prior-knowledge of students in the system thinking the concept of plant classification system in the low category. Only 31% of students can describe the components and processes on the system, 24% of students can identify component relationships on the system, 44% of students understand the dynamic behavior of the system, 25% of students can manage system components and processes within the relationship framework and 25% students can understand the nature of the system. Low prior-knowledge of students is due to the tendency of students who think is not comprehensive and can not connect between components to form system when system thinking is required for students to high thinking order.